Application of the measurement of the natural abundance of stable isotopes in viticulture: a review. (30th December 2014) - Santesteban, L.G.; Miranda, C.; Barbarin, I.; Royo, J.B.
Abstract: The study of the natural abundance of stable isotopes in grapevine organs and tissues started in the late 1970s and, since then, a significant body of research has analysed how cultivar, rootstock, climate, soil and growing conditions affect the relative proportion of the stable isotopes of carbon (δ 13 C), oxygen (δ 18 O) and hydrogen (δD) in grapevine organs. Besides, some research has been devoted to the study of the isotope ratios of nitrogen (δ 15 N), strontium (δ 87 Sr), boron (δ 11 B) and sulfur (δ 34 S) in vineyards. This review presents the state of the art of stable isotope determination in viticulture, and outlines some approaches that, to date, have not been considered in viticulture and that could be applied in future research.